En uppföljning av floran i Enköpings vattenpark : kan anlagda våtmarker med vattenrening som huvudsyfte bidra till naturvård och biologisk mångfald? - Hedberg, Erika (SLU/Dept. of Ecology, 2008)
Wetlands are important ecosystems and form habitat for both common and threatened species. In Sweden, as well in many other places on earth, there is a lack of wetlands. There is an expressed will to adjust this lack through restoration of wetlands with reduced function and through construction of new wetlands. Follow-ups and evaluations are important steps to optimize these actions. The wetland Vattenparken was constructed 1999 – 2000 for treatment of surface water. During the construction a big effort was made to ensure the benefits for biodiversity, mainly through planting of wetland vegetation and introduction of wetland plant species.